2022
DOI: 10.1097/wnn.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dopaminergic Therapy on Impulse Control Disorders in Patients With a Prolactinoma

Abstract: Background: Studies have reported an increase in the incidence of impulse control disorders (ICDs) in patient groups treated with dopamine agonists (DAAs), especially in Parkinson disease (PD). However, very few studies have reported on ICDs in individuals with a prolactinoma who were treated with DAAs.Objective: To see whether a DAA by itself causes ICDs in individuals with a prolactinoma by controlling the susceptibility to impulsivity by excluding individuals with other risk factors for ICDs. Method:We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…In 2019, a multicenter study detected an ICD prevalence of 17%, with hypersexuality being the most common type, occurring mostly in males, as in our study [ 18 ]. Another study found a prevalence of 25.8% in the cabergoline-treated group as compared to 15% in the non-cabergoline-treated group, and this did not reach statistical significance, but compared to our study, the prevalence of ICDs in the control group was much higher [ 19 ]. The study by Bancos et al had comparable results, with 24.8% in patients versus 17.1% in the control group, but was non-significant [ 20 ].…”
Section: Discussioncontrasting
confidence: 98%
“…In 2019, a multicenter study detected an ICD prevalence of 17%, with hypersexuality being the most common type, occurring mostly in males, as in our study [ 18 ]. Another study found a prevalence of 25.8% in the cabergoline-treated group as compared to 15% in the non-cabergoline-treated group, and this did not reach statistical significance, but compared to our study, the prevalence of ICDs in the control group was much higher [ 19 ]. The study by Bancos et al had comparable results, with 24.8% in patients versus 17.1% in the control group, but was non-significant [ 20 ].…”
Section: Discussioncontrasting
confidence: 98%
“…2 illustrates the notably wide distribution in the observed frequency of ICDs across various published studies involving patients with PAs/disorders undergoing DA therapy. [8][9][10][11][12][13][14][15][16][17][18][19] This variation can be attributed to many factors, as demonstrated in ►Table 1. [7][8][9][10][11][12][13][14][15][16][17][18][19] These factors include disparities in study demographics (patients with prolactinomas vs. other adenomas or pituitary disorders), sex distribution, study methodologies (cross-sectional vs. prospective designs), the inclusion or exclusion of wellmatched control groups, and nuances in DA therapy (type, duration, dosage, current or prior usage, cumulative dosage).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19] This variation can be attributed to many factors, as demonstrated in ►Table 1. [7][8][9][10][11][12][13][14][15][16][17][18][19] These factors include disparities in study demographics (patients with prolactinomas vs. other adenomas or pituitary disorders), sex distribution, study methodologies (cross-sectional vs. prospective designs), the inclusion or exclusion of wellmatched control groups, and nuances in DA therapy (type, duration, dosage, current or prior usage, cumulative dosage). 6 Furthermore, variations in assessment tools (both in quantity and type), whether assessments were self-reported or conducted by health care professionals or experts in ICDs and the presence of additional risk factors for ICD development (smoking, alcohol consumption, history of depression/ mental illness, and family predisposition to mental health conditions) can all contribute to the frequency of ICD.…”
Section: Introductionmentioning
confidence: 99%